Narcisismo na rede : o espetáculo do hiperindivíduo nas páginas do Facebook - Lima, Nilma Regina Mendes (2016)
Based on the assumption that a large number of the contemporary social relations is the result from a social imaginary that influences and is influenced by one of the strongest hypermodernity imaginary technologies – the social networking websites – this research aims to carry out a study about digital narcissism phenomenon, understanding it as a manifestation of hyper-spectacle that the hypermodern individual, here referred as hyper-individual, performs in these websites, especially in the social network Facebook. Thus, from the theoretical basis, endorsed by the imaginary notions, hypermodernity, hyper-individual, spectacle, hyperspectacle and social networks presented by authors such as Durand, Maffesoli, Lipovetsky, Debord, Silva and Recuero, a correlation among theories and a confrontation between them with the posts of individuals from network were held to, from this correlation, understand how, through what kind and under what conditions, this phenomenon hypermodern imagery is being developed in contemporary times. Therefore, a hybrid methodological contributions support this study, it consists on the bibliographical research, comprehensive sociology, netnography and Content Analysis, which was crucial so that we achieve the results described herein.